Transnasal Esophagoscopy—Our Experience - Rocke, John; Ahmed, Shadaba (International Archives of Otorhinolaryngology, 2019)
Introduction Transnasal esophagoscopy (TNE) is a widely used tool both in the diagnosis and treatment of patients presenting complaints within the head and the neck. This is because this investigative adjunct examination provides the advantage of visualizing above the level of the cricopharyngeus muscle when compared to the more widely used esophagogastroduodenoscopy (EGD).Objectives We have assessed if the implementation of TNE within a district general hospital (DGH) was feasible, and investigated if the resources of our patients could be better directed away from other investigations such as barium swallow and EGD in favor of this novel technique. The TNE technique has been largely applied in central teaching hospitals within the United Kingdom, but there are still no published reports of a DGH investigating its applicability in this smaller-sized clinical environment.Method We have analyzed our theater database to find all the patients who had undergone TNE, and recorded their reason for presenting, the preceding investigations, and the procedural findings.Results In most cases, the TNE was conducted without technical issues, and we were able to identify positive findings in 43% of the patients who underwent Esophagogastroduodenoscopy (EGD). We were able to treat patients successfully during the investigation when a cricopharyngeal stricture or narrowing was found. A normal EGD did not preclude further investigations with TNE. All but one of our patients were treated as day-case procedures.Conclusion Transnasal esophagoscopy can be successfully delivered within a DGH. A previous EGD does not mean that the TNE will not reveal positive findings due to its superior visualization of the pharynx and the upper esophagus.
Keywords: Endoscopy; esophagoscopy; deglutition disorders